Incidence Of Acute Kidney Injury In Mild, Moderate And Severe Cases Of Coronavirus Disease - Mahmud, Mahvesh; Kumar, Ashok; Baqai, Khurram (Journal of Rawalpindi Medical College, 2023)
Objective: The purpose of this research was to determine the incidence of Acute Kidney Injury (AKI) in COVID-19-affected patients Methods: This retrospective cohort study was conducted at Ziauddin Hospital Clifton Campus from June to December 2020. Adult patients with AKI or acute-on-chronic kidney disease (ACKD) were included in a retrospective study. Patients infected with SARS-CoV2 and renal involvement were directed towards the ICU/Nephrology departments which have the expertise to perform laboratory analysis, radiography and institution of treatment. Supplemental oxygen use was documented. The research also assessed information about therapy (antivirals, immunomodulators, RRT) and results (renal function recovery or death). Results: After excluding patients with obstructive AKI, a total of 180 (mean age 50.1 years) of 104 males and 76 females were included in the research. 120 patients were found to have prerenal, and 60 had intrinsic AKI with significant differences between mild, moderate, and severe cases (p=0.004). Acute kidney injury (AKI) survivors had a complete recovery rate of 70%, a partial recovery rate of 22%, and a hemodialysis dependency rate of 8%. Conclusion: Patients with severe COVID-19 infection often develop more severe AKI, and those in the severe or critical stages often exhibit proteinuria and dipstick hematuria. Long-term follow-up for COVID-19 patients should be done to evaluate its influence on renal outcome, and larger samples are required to elucidate the association between COVID-19 and renal damage. Keywords: Coronavirus Disease, Renal Replacement Therapy, proteinuria, dipstick hematuria